Analisis Komunikasi Strategis Public Relations Bank Indonesia dalam Sosialiasasi Kebijakan Moneter kepada Stakeholders - Almira Nur Fauziah; Dian Hutami Rahmawati (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This research aims to analyze Bank Indonesia's Public Relations (PR) communication strategy in socializing monetary policy to external stakeholders. This study used a qualitative descriptive approach with Cutlip, Center, and Broom strategic communication models as an analysis framework. The research results show that Bank Indonesia's PR implements four stages of communication strategies: finding the fact and defining the problem, planning and programming, taking action and communicating, and evaluation. PR Bank Indonesia maps stakeholders, including parliament, government, banking, market players, academics, mass media, and the general public. Omnichannel communication that integrates Above the Line (ATL), Below the Line (BTL), and Through the Line (TTL) is used to reach audiences with segmented approaches. Strategy evaluation is conducted through surveys, FGD, and feedback analysis from the community on social media and mass media as well as annual evaluation through EVAKOM (Communication Evaluation). This study found that people's demographic diversity is a major challenge, so a flexible approach is needed to simplify monetary policy information to make it easier to understand.